Utilization coal-bottom ash and sludge from wastewater for fabricating porous ceramic PM filter: properties and filtering performance - W. Prasertsin; Mettaya Kitiwan; Mana Rodchom; Duangduen Atong; Supawan Vichaphund (International Journal of Environmental Science and Technology, 2025)
In this work, coal-bottom ash and sludge from wastewater obtained from local plant in Thailand were used as raw materials to fabricate porous ceramic materials using extrusion method for particulate matter (PM) filtration. The influence of the sludge addition (0–40 wt%) and sintering temperature (1000–1200 °C) on physical and mechanical properties of porous ceramic materials was investigated. The addition of sludge led to a decrease in the bulk density of BA-(10–40 wt%) SL ceramic samples sintered at all sintering temperatures due to high level of porosity generated from the gas evolving inside ceramic samples. The maximum bulk density of BA-(10–40 wt%) SL samples, ranging from 1.22 to 1.97 g/cm3, was obtained at 1150 °C. The porous BA-SL ceramic filters containing 20–40 wt% sludge and sintered at 1150 °C exhibited high open porosity (> 50%) while maintaining good mechanical strength (1.20–2.31 MPa). Additionally, these filters primarily featured small pore sizes between 5 and 30 μm, making them suitable for micron-level filtration and, consequently, effective for PM filtration applications. The BA-(20–40 wt%) SL ceramic filters achieved over 95% efficiency for PM2.5 and PM10, with an acceptable pressure drop < 700 Pa. Among the tested samples, the BA-SL20 filter, which had a high porosity of 50.60% with interconnected pores within the ceramic structure, an average pore size of 15.23 μm, and a compressive strength of 2.31 MPa, exhibited the highest removal efficiency of 99.48% for PM2.5 and 99.29% for PM10 at a pressure drop of 622 Pa. These results suggest that coal bottom ash and sludge from industrial waste can be effectively utilized as alternative raw materials for producing ceramic filters for PM removal applications.
Keywords: Recycling and utilization of industrial and municipal waste in materials production; Advanced ceramic materials synthesis; Recycling and Waste Management Techniques